Chi-Square Analysis of the Preference of Packaged Food on the Basis of Household Income of the Respondents: The Impact of Household Income on Consumer Preference for Packaged Food in Retail Marketing (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Retail Marketing defined as“individuals or groups, acquiring, using and disposing of products, services,ideas or experiences” (Arnould, Price & Zinkha, 2004). There are numbers ofdifferent theories explaining Retail Marketing (Statt, 1997; Blackwell,Minrard, and Engel, 2006; Chaudhuri, 2006) and a huge amount of literaturecurrently exists (Grunert 2002; Botonaki, Ploymeros, Tsakorodou, & Mattas,2006; Friese, Wanke, and Plessner, 2006). There are different number ofcharacteristics, which can impact on Retail Marketing Majorityof the respondents in the middle-income segments are in both the categories whodo packaged food and who do not do. However in the upper income segment, the preferencefor doing packaged food is more skewed in comparison to their counterparts. Theapplication of chi-square highlights significant association between thevariables